Effect of Technical Parameters of Electric Low Voltage Devices of the Shop Power Supply Systems on their Reliability Characteristics - Gracheva E.I.; Ivshin I.V.; Gorlov A.N.; Alimova A.N. (Problems of the Regional Energetics)
The article deals with an integrated approach to the study of the functioning efficiency of low-voltage switching devices as elements of shop networks during their operation. Based on the results of experimental studies of the contact connections of devices using a thermal imaging equipment, a new criterion is offered for the estimation of the technical condition of devices, namely, the coefficient of actual multiplicity exceeding the contact resistance under operating conditions. Its calculated numerical values for circuit breakers, contactors, magnetic starters, knife switches and batch switches are determined that allow evaluating their technical condition and operation. They also prevent the development of defects in the switching equipment and failures and make it possible to use the developed criterium for the supplemental regulation pe-riods of investigations of switching devices. An algorithm and a method have been elaborated for a comprehensive assessment of the functioning efficiency of the switching low-voltage de-vices, which allows establishing a relationship between the probability of uptime and the contact resistance of devices considering the number of switching cycles. The contact resistance is considered as a random function of the number of switching cycles. The studies carried out according to the developed algorithm with the identification of the functional relationship between the contact resistance parameters and the probability of failure-free operation of the devices in-stalled on the lines of the networks allow us to evaluate the technical condition of the equipment. The amount of the electricity losses and characteristics reliability of the internal power supply systems can also be specified.